PENGARUH KONEKSI POLITIK DAN TATA KELOLA PERUSAHAAN TERHADAP BIAYA AUDIT - Sabda Surya Daniel Simanjuntak; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2021)
This study aims to determine the extent of the ability of political connections in influencing audit costs and to determine the extent to which corporate governance capabilities are assessed using the corporate governance perception index in influencing audit fees. This analysis is also supported by several control variables namely company size, return on assets, and the public accounting firm used. The sampling method used in this study was purposive sampling, the number of companies sampled for 9 companies with observations for 4 years so that a total of 36. Data processing used by researchers is multiple regression analysis. The results of this study indicate that political connections have a positif effect on rejected audit fees. Meanwhile corporate governance which is assessed using the corporate governance perception index has a negative effect on accepted audit fees.